The Effect of Back Massage on The Sleep Quality of Trimester III Primigravida Pregnant Women in Puskesmas Talaga Jaya - Dwi Nur Octaviani Katili; Rizky Nikmathul Husna Ali; Riskawaty Abidju (Journal La Medihealtico, 2020)
The quality of sleep on pregnant women affected their condition during pregnancy. A decrease in sleep duration in pregnant women can cause a decrease in concentration, fatigue, body aches, losing the mood to work, and having a tendency to be emotional. The aim of the study was to determine the effect of back massage on the sleep quality of trimester III primigravida pregnant women in Puskesmas Talaga Jaya. The research design was a quasi experimental design with a nonequivalent control group design. The research sample was 20 pregnant women with the sampling technique using purposive sampling. From the results of the independent t test, it shows that there is a difference between the experimental group and the control group on the decrease in sleep quality with a p value of = 0.000 α <(0.05). Therefore, it can be concluded that back massage is more effective in increasing sleep quality of those given treatment than those without given treatment.